Enhancing the yield, fruiting body traits, and nutritional properties of five major edible fungi through the exploitation of ginger straw substrate - Yan Zhang; Yihui Wang; Yuting Li; Panmeng Wang; Li Wang; Zhuang Li (Frontiers in Nutrition)
Edible fungi, as nutritious foods in healthy diets, have gained popularity among consumers. The expansion of the edible fungi cultivation scale led to a shortage of cultivation substrate, making the development and utilization of new substrates a research hotspot. Ginger straw, the main byproduct in the ginger planting process, boasts a huge yield. In this study, ginger straw substrate (GSS) was assessed for the first time for cultivating five major edible fungi. The results indicated a significant improvement in biological efficiency (BE) with GSS, increased by 1.22–64.81%. In terms of nutritional properties, the GSS not only significantly increased the crude protein content (0.36~10.6%) and reduced sugar content (0.01~1%), crude fiber content (0.14~3.87%), and mineral level (The maximum increases were 217.02 mg/kg for calcium, 4.74 mg/kg for magnesium, and 44.08 mg/kg for iron) but also positively affected the total antioxidant capacity and composition of flavor-contributing amino acids. These results provide a scientific basis for cultivating edible fungi with ginger straw and offer a new way for edible fungi substrate selection.